2018
DOI: 10.1111/hequ.12168
|View full text |Cite
|
Sign up to set email alerts
|

Transnational research training: Chinese visiting doctoral students overseas and their host supervisors

Abstract: International experience during doctoral training is critical in improving the quality of research training and establishing international networks. This study makes an original contribution to the understanding of the research partnership between visiting doctoral students and their supervisors. The current research draws upon empirical evidence from a survey, semi‐structured interviews and CV analysis of Chinese visiting doctoral students sponsored by the China Scholarship Council. Findings confirm the good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 37 publications
1
13
0
1
Order By: Relevance
“…Regarding the establishment and maintenance of Sino-Swiss international cooperation relationships, trust between doctoral students, postdoctoral researchers, and visiting doctoral students and their supervisor in Switzerland presents different degrees of difficulty, with varying characteristics. This research confirms the findings of previous studies on potential conflicts that may arise during international scientific research collaboration in terms of intellectual property ownership, sequence of authorship, and scientific discovery priority (Floyd, Schroeder and Finn, 1994;Katz and Martin, 1997;Shen, 2018). When parties do not belong to the same organization, conflicts in knowledge production caused by a lack of trust are likely to occur.…”
Section: Conclusion and Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Regarding the establishment and maintenance of Sino-Swiss international cooperation relationships, trust between doctoral students, postdoctoral researchers, and visiting doctoral students and their supervisor in Switzerland presents different degrees of difficulty, with varying characteristics. This research confirms the findings of previous studies on potential conflicts that may arise during international scientific research collaboration in terms of intellectual property ownership, sequence of authorship, and scientific discovery priority (Floyd, Schroeder and Finn, 1994;Katz and Martin, 1997;Shen, 2018). When parties do not belong to the same organization, conflicts in knowledge production caused by a lack of trust are likely to occur.…”
Section: Conclusion and Discussionsupporting
confidence: 88%
“…First, with rare exceptions (e.g., Ynalvez and Shrum, 2009;Murakami, 2014;Jiang and Shen, 2019), most studies on international scientific research cooperation emphasize the perspective of science and technology policy without paying adequate attention to the education system and educational mobility. Second, when explaining the relationship between academic mobility and international scientific research cooperation, most studies either highlight the role of scientific internationalism (Shen, 2018) or the differences in scientific research training systems (mentor guidance styles and modes of study) to explain whether international cooperation can be maintained (Ynalvez and Shrum, 2009). According to Ynalvez and Shrum (2009), when Filipino scholars return to their home country after completing their postgraduate training in the United States, Australia, or Japan, they are more likely to cooperate with Japanese scholars owing to more frequent interactions with Japanese supervisors than with American or Australian supervisors during their graduate studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuing with the example of Chinese scholarships, several authors pointed out that individuals educated in the STEM fields were recruited back home with promise of world-class laboratories, salary supplements, and financial support for their housing and children’s education (Zha & Wang, 2018). Shen (2018) wrote that Chinese doctoral students “leverage the superior faculty resources and research facilities overseas” (p. 224) to bring knowledge back home for economic development. While much of the research focuses on STEM fields, Chalid (2014) has noted that scholarships also develop important “soft skills” and intercultural competency.…”
Section: Resultsmentioning
confidence: 99%
“…This situation is in theory a win-win for the visiting PhD students and for the hosting PhD supervisor and his or her students. A previous study found that more than 60% of Chinese exchange doctoral students in a STEM field published papers with their host supervisors (Shen, 2018). However, if the hosting university overemphasizes this practice, one supervisor may be supervising several PhD students from his or her own university in addition to those visiting.…”
Section: Contextual Factorsmentioning
confidence: 99%